ANALISIS PELANGGAN TERHADAP METHODE SHARING EKONOMI TRANSPORTASI ONLINE DI BANDA ACEH - Cut Devi Maulidasari (JURNAL EKOMBIS, 2018)
This research analyzes how consumers conduct online transportation in Banda Aceh using economic sharing method by comparing technology acceptance Model (TAM) with planned behavioral theory (TPB) and combination of both TAM and TPB